Clinical characteristics and treatment outcome in p16 negative anal cancer - Catherine Burgos; Calin Radu; Sofia Heyman; Nina Cavalli-Björkman; Peter Nygren (Acta Oncologica)
Background: Anal squamous cell carcinoma (ASCC) is linked to human papillomavirus infection with p16 being positive in about 85% of cases. Overall survival (OS) of ASCC is 60%–80%. Prognosis in p16 negative (p16-) ASCC is worse with an OS of 30%–60%. It is important to elucidate differences in p16+ and p16- ASCC characteristics and outcome.